Elevated Sodium Pump α3 Subunit Expression Promotes Colorectal Liver Metastasis via the p53-PTEN/IGFBP3-AKT-mTOR Axis - Wu, Di; Yu, Hong-Qiang; Xiong, Hao-Jun; Zhang, Yu-Jun; Lin, Xiao-Tong; Zhang, Jie; Wu, Wu; Wang, Teng; Liu, Xiao-Yu; Xie, Chuan-Ming (Frontiers in Oncology, 2021)
The sodium pump α3 subunit is associated with colorectal liver metastasis. However, the underlying mechanism involved in this effect is not yet known. In this study, we found that the expression levels of the sodium pump α3 subunit were positively associated with metastasis in colorectal cancer (CRC). Knockdown of the α3 subunit or inhibition of the sodium pump could significantly inhibit the migration of colorectal cancer cells, whereas overexpression of the α3 subunit promoted colorectal cancer cell migration. Mechanistically, the α3 subunit decreased p53 expression, which subsequently downregulated PTEN/IGFBP3 and activated mTOR, leading to the promotion of colorectal cancer cell metastasis. Reciprocally, knockdown of the α3 subunit or inhibition of the sodium pump dramatically blocked this effect in vitro and in vivo via the downregulation of mTOR activity. Furthermore, a positive correlation between α3 subunit expression and mTOR activity was observed in an aggressive CRC subtype. Conclusions: Elevated expression of the sodium pump α3 subunit promotes CRC liver metastasis via the PTEN/IGFBP3-mediated mTOR pathway, suggesting that sodium pump α3 could represent a critical prognostic marker and/or therapeutic target for this disease.